FACTORS AFFECTING INTENTION TO PURCHASE SPORT SERVICE FOR TAX REDUCTION ACCORDING TO THE YEAR 2017 ECONOMY STIMULATION MEASURE - Phiboonphon, Phatsamon; Kutintara, Issadee; Terason, Sid (Academic Journal of Thailand National Sports University, 2019)
The purpose of this research was to study the factors affecting intention to purchase sports services for tax deduction according to the year 2017 economic stimulus measure. A questionnaire method was used to collect data from the individual tax Thai age 23 years of 400 people from the private fitness centers in Bangkok and vicinity. This study identified the significant factor that affect consumers’ purchase intentions toward using content analysis of statistics such as the median, percentage and multiple regression analysis. The result was found that the society and culture positively affected on the intended purchase of sports services for tax stimulus measures. Therefore, the benefit of this study can be used as a reference for sports services to plan marketing strategies.